Same day diagnosis of Down's syndrome and sex in single cells using multiplex fluorescent PCR. Issue 3 (June 1998) - Findlay, I; Matthews, P; Tóth, T; Quirke, P; Papp, Z
Abstract : The major reason for prenatal diagnosis lies in the detection of trisomies, particularly trisomy 21 (Down's syndrome). Current techniques require lengthy laboratory procedures and high costs. Furthermore, diagnosis is often not possible if the sample is of small size or is contaminated. An alternative method, quantitative fluorescent polymerase chain reaction (PCR) of short tandem repeats (STRs), can also be used to diagnose trisomies and it has the advantage that a result is obtained within five to eight hours. However, this method is currently limited to relatively large amounts of sample, which restricts diagnostic confidence and value. Recently, genetic diagnosis using fluorescent PCR has been applied at the single cell level but is limited to sex or single gene defect diagnosis. This study, using quantitative multiplex fluorescent PCR, provides for the first time simultaneous diagnosis and confirmation of sex and trisomy in single cells. Two markers for chromosome 21 increase diagnostic confidence, informativeness, and confirmation. This system is rapid (five hours), reliable, and accurate and we believe that it will be more cost effective than alternative methods. The technique has direct application to preimplantation genetic diagnosis, early prenatal diagnosis, and other diagnostic systems where sample size is limited.